An extended catalog of integrated prophages in the infant and adult fecal microbiome shows high prevalence of lysogeny - Dikareva, Evgenia; Matharu, Dollwin; Lahtinen, Emilia; Kolho, Kaija-Leena; De Vos, Willem M.; Salonen, Anne; Ponsero, Alise J. (Frontiers in Microbiology, 2023)
Background and aims The acquisition and gradual maturation of gut microbial communities during early childhood is central to an individual’s healthy development. Bacteriophages have the potential to shape the gut bacterial communities. However, the complex ecological interactions between phages and their bacterial host are still poorly characterized. In this study, we investigated the abundance and diversity of integrated prophages in infant and adult gut bacteria by detecting integrated prophages in metagenome assembled genomes (MAGs) of commensal bacteria. Methods Our study included 88 infants sampled at 3 weeks, 3 months, 6 months, and 12 months (n = 323 total samples), and their parents around delivery time (n = 138 total samples). Fecal DNA was extracted and characterized by using shotgun metagenomic sequencing, and a collection of prokaryotic MAGs was generated. The MAG collection was screened for the presence of integrated bacteriophage sequences, allowing their taxonomic and functional characterization. Results A large collection of 6,186 MAGs from infant and adult gut microbiota was obtained and screened for integrated prophages, allowing the identification of 7,165 prophage sequences longer than 10 kb. Strikingly, more than 70% of the near-complete MAGs were identified as lysogens. The prevalence of prophages in MAGs varied across bacterial families, with a lower prevalence observed among Coriobacteriaceae, Eggerthellaceae, Veillonellaceae and Burkholderiaceae, while a very high prevalence of lysogen MAGs were observed in Oscillospiraceae, Enterococcaceae, and Enterobacteriaceae. Interestingly for several bacterial families such as Bifidobacteriaceae and Bacteroidaceae, the prevalence of prophages in MAGs was higher in early infant time point (3 weeks and 3 months) than in later sampling points (6 and 12 months) and in adults. The prophage sequences were clustered into 5,616 species-like vOTUs, 77% of which were novel. Finally, we explored the functional repertoire of the potential auxiliary metabolic genes carried by these prophages, encoding functions involved in carbohydrate metabolism and degradation, amino acid metabolism and carbon metabolism. Conclusion Our study provides an enhanced understanding of the diversity and prevalence of lysogens in infant and adult gut microbiota and suggests a complex interplay between prophages and their bacterial hosts.